Objectification of Women in Milkman Novel by Anna Burns (Universitas Pamulang, 2023)
This study strives to disclose women’s objectification in literary work through the lens of feminism. The object of this study is a novel entitled Milkman (2018) by Anna Burns. This study strives to classify the forms of objectification experienced by female characters and how they deal with it. This study employed a qualitative approach and analyzed in the form of essays. Therefore, this study uses Nussbaum’s (1999) objectification and Gooden’s (2004) resistance ideas to examine the object of the study. This study discovered that Middle Sister was subject to six out of seven types of objectifications by male characters. They are instrumentality, denial of autonomy, inertness, violability, ownership, and denial of subjectivity. In addition, this study also discovered that Eldest Sister was subject to two different types of objectifications by her husband. They are a denial of autonomy and inertness. However, this study also uncovers how these women choose to resist objectification. They deal with it by relying on other women, avoiding, and fighting back against the source of the problem. Mainly, the data findings disclose that the object is a manifestation of Northern Ireland women’s lives in the late nineteenth century and centered on the issue of women’s objectification. Keywords: feminism, Northern Ireland women, resistance, women’s objectification